2017
DOI: 10.1111/bcpt.12743
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the Effects of Quercetin on Mouse Myocardium

Abstract: Quercetin is a plant flavonoid with several biological activities. This study aimed to describe quercetin effects on contractile and electrophysiological properties of the cardiac muscle as well as on calcium handling. Quercetin elicited positive inotropism that was significantly reduced by propranolol indicating an involvement of the sympathetic nervous system. In cardiomyocytes, 30 μM quercetin increased I at 0 mV from -0.95 ± 0.01 A/F to -1.21 ± 0.08 A/F. The membrane potential at which 50% of the channels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Recently, Santos et al reported a study similar to our present study, in which QCT enhanced both the sarcomere contraction and CaT in mice isolated cardiomyocytes [31]. Surprisingly, however, they did not refer to the intrinsic fluorescence of QCT and requisite correction of the F380 intensity to reconcile the apparently contradistinctive phenomenon of enhanced cardiomyocyte contractility with decreased CaT in experiments using Fura-2.…”
Section: Discussionsupporting
confidence: 57%
“…Recently, Santos et al reported a study similar to our present study, in which QCT enhanced both the sarcomere contraction and CaT in mice isolated cardiomyocytes [31]. Surprisingly, however, they did not refer to the intrinsic fluorescence of QCT and requisite correction of the F380 intensity to reconcile the apparently contradistinctive phenomenon of enhanced cardiomyocyte contractility with decreased CaT in experiments using Fura-2.…”
Section: Discussionsupporting
confidence: 57%
“…Using an EPC-9.2 patch-clamp amplifier (HEKA Electronics, Rheinland-Pfalz, Germany) we recorded voltage-dependent L-type Ca 2+ current (I Ca,L ) in the whole-cell voltage-clamp configuration of the patch-clamp technique [15, 16]. Ventricular cardiomyocytes were isolated from guinea pig heart by enzymatic digestion as described by Shioya [17] with minor modifications (reduction of enzyme time in the first and second tubes for 6 min).…”
Section: Methodsmentioning
confidence: 99%
“…The composition of pipette solution was as follows (in mM): 120 CsCl, 20 TEACl, 5 NaCl, 10 HEPES and 10 EGTA, and 1 MgCl 2 (pH was set to 7.2 using CsOH) and external solution was as follows (in mM): 150 TEACl, 0.5 MgCl 2 , 1.8 CaCl 2 , 10 HEPES, and 11 glucose (pH 7.4 set using TEA(OH)). The holding potential was set at -80 mV and prepulses were elicited from -80 mV to -40 mV for 50 ms (every 10 s) to inactivate any remnant Na + and/or T-type Ca 2+ channels [16]. Then, it was applied a test pulse to 0 mV during 300 ms to directly measure I Ca,L .…”
Section: Methodsmentioning
confidence: 99%
“…This substance also reduces ROS generation and increases the endogenous antioxidant enzymes and non-enzymes (see above) [ 168 ]. Santos et al [ 169 ] have shown that quercetin increases I Ca under β-adrenoceptor stimulation and intracellular Ca 2+ transient without changing Ca 2+ sparks [ 112 ]. Anthocyanins are a water-soluble pigment subgroup mainly found in flavonoid groups that are ranging from red to blue colors in many kinds of plants, flowers, and seeds, etc.…”
Section: Exogenous Natural Antioxidants To Protect Cardiac Muscle From Oxidative Stressmentioning
confidence: 99%
“…Anthocyanins are a water-soluble pigment subgroup mainly found in flavonoid groups that are ranging from red to blue colors in many kinds of plants, flowers, and seeds, etc. [ 169 ]. The strength of antioxidation among anthocyanins is controlled by their differences in chemical structure, such as the number and location of conjugation groups, hydroxyl groups, glycosylation, donor electrons in the ring structure, as well as the aromatic group’s capacity to sustain the disappearance of electrons [ 170 , 171 ].…”
Section: Exogenous Natural Antioxidants To Protect Cardiac Muscle From Oxidative Stressmentioning
confidence: 99%